Premature delivery influences the immunological composition of colostrum and transitional and mature human milk (2011)
Human breast milk is the ideal nutrition for the newborn, and in addition to its nutritional contribution, necessary for infant growth and development, it contains various immune bioactive factors that confer some of the numerous beneficial effects of breastfeeding. The current study analyzed the concentrations of IgA, growth factors such as epidermal growth factor (EGF), TGFb1, and TGFb2, cytokines IL-6, IL-8, IL-10, IL-13, and TNFa, and TNF-receptor I (TNF-RI) in colostrum and transitional and mature milk from mothers with mature, premature, and very premature infants. Human milk samples were collected from mothers delivering at term (T), preterm (PT), and very preterm (VPT). Milk from all the mothers was collected at 3 different time points after delivery corresponding to colostrum and transitional and mature milk.